Development of a chemically defined medium for Planctopirus limnophila to increase biomass production - Oscar Claudius Kruppa (Elsevier, 2021)
Background: Planctomycetes is a phylum of biofilm-forming bacteria with numerous biosynthetic gene clusters, offering a promising source of new bioactive secondary metabolites. However, the current generation of chemically defined media achieves only low biomass yields, hindering research on these species. We therefore developed a chemically defined medium for the model organism Planctopirus limnophila to increase biomass production. Results: We found that P. limnophila grows best with a 10 mM sodium phosphate buffer. The replacement of complex nitrogen sources with defined amino acid solutions did not inhibit growth. Screening for vitamin requirements revealed that only cyanocobalamin (B12) is needed for growth. We used response surface methodology to optimize the medium, resulting in concentrations of 10 g/L glucose, 34 mL/L Hutner’s basal salts, 23.18 mM KNO3, 2.318 mM NH4Cl and 0.02 mg/L cyanocobalamin. The analysis of amino acid consumption allowed us to develop a customized amino acid solution lacking six of the amino acids present in Aminoplasmal 10%. Fed-batch cultivation in a bioreactor using the optimized medium achieved a final ΔOD600 of 46.8 ± 0.5 after 108 h, corresponding to a cell dry weight of 13.6 ± 0.7 g/L. Conclusions: The optimized chemically defined medium allowed us to produce larger amounts of biomass more quickly than reported in earlier studies. Further research should focus on triggering P. limnophila biofilm formation to activate the gene clusters responsible for secondary metabolism.How to cite: Kruppa OC, Gerlach D, Fan R, et al. Development of a chemically defined medium for Planctopirus limnophila to increase biomass production. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.09.002.